Programming Experience and Computational Thinking Skills: A Study on Prospective PPG Pre-Service Informatics Engineering Teachers - Maya Sari Wahyuni; Muhammad Isbar Pratama; Nurul Mukhlisah Abdal (Jurusan Teknik Informatika dan Komputer, 2025)
Computational Thinking (CT) is a core competency emphasized in Indonesia’s Kurikulum Merdeka, yet variations in pre-service teachers’ programming backgrounds may influence their CT readiness. This study examined the relationship between programming experience and CT skills among pre-service informatics teachers enrolled in the PPG Prajabatan program at Universitas Negeri Makassar. Using a correlational design, data were collected from 153 participants, with programming experience measured through a validated Python-based questionnaire and CT skills assessed using Bebras tasks covering key CT dimensions. The findings show a strong positive association between programming experience and CT performance, with active project involvement and frequent practice emerging as the most influential components. Programming experience also served as a significant predictor of CT skills, accounting for a substantial proportion of variance. These results highlight the importance of sustained programming engagement in supporting CT development and suggest that project-oriented coding activities should be more systematically integrated into pre-service informatics teacher education and PPG curricular practices